Cochlear implantation in young children: effects of age at implantation and communication mode. - Kirk KI; Miyamoto RT; Ying EA; Perdew AE; Zuganelis H (Volta Review, 2002)
This study examined the effects of age at implantation on the development of communication abilities in early implanted children. The 106 participants were prelingually deafened and used current cochlear implant technology. The children were administered a battery of speech and language outcome measures prior to implantation and again at successive 6-month postimplant intervals. A mixed model analysis was used to examine the rate of growth in word recognition and language skills as a function of age at time of implantation. Results revealed significant improvements in communication skills over time. Spoken word recognition improved at a faster rate in the children implanted at 5 years of age or older, possibly because they were more likely to be familiar with the test vocabulary. In addition, the rate of spoken word development was significantly greater for children who used oral communication (OC) than for children who used Total Communication (TC). Age effects on the development of receptive and expressive language differed from those on spoken word recognition. Earlier implanted children demonstrated superior language abilities. Children implanted prior to 2 years of age had significantly faster rates of receptive vocabulary and language development than later-implanted children. Furthermore, children implanted prior to age 2 had superior expressive language abilities compared with those implanted after that age. There were no significant differences in rates of language development between the oral and Total Communication groups.